Individual Differences From His Learning Style And The Implications In Learning At Universities - Alchonity Harika Fitri; Jamaris; Solfema (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
The study of individual differences in education explains differences related to differences in thinking, feeling and acting among students in a class. Educational levels from elementary school to college level have differences in learning styles. Effective learning is able to accommodate student needs. This is in accordance with the opinion of Sugihartono (2007) which says that one of the characteristics of effective learning is if learning can respond to student needs. Special needs relate to the uniqueness or differences between students. This individual difference in the learning process is the task of educators in understanding students, because they face students with various individual differences. This difference is normal and unavoidable. As a good teacher, the teacher cannot eliminate these differences by assuming all students are equal. Therefore, efforts are needed to address the differences of each student. Based on the study of literature from previous studies, it was found that students need to be considered in the learning process so that students can easily understand the learning material presented by the lecturer in the classroom.